EGR-1/Bax Pathway Plays a Role in Vitamin E δ-Tocotrienol-induced Apoptosis in Pancreatic Cancer Cells - Wang, Chen (J Nutr Biochem, 2015)
The anticancer activity of δ-tocotrienol, a bioactive vitamin E present in whole grain cereals, annatto beans, and palm fruit, is strongly dependent on its effect on the induction of apoptosis. δ-Tocotrienol-induced apoptosis is associated with consistent induction in the expression of the pro-apoptotic protein Bax. The molecular mechanism by which δ-tocotrienol regulates Bax expression is unknown. We carried out a DNA microarray study that identified δ-tocotrienol induction of the zinc finger transcription factor, EGR-1, in pancreatic cancer cells. Here, we provide evidence linking δ-tocotrienol-induced apoptosis in pancreatic cancer cells to EGR-1 regulation of Bax expression. Forced expression of EGR-1 induces Bax expression and apoptosis in pancreatic cancer cells. In contrast, knockdown of δ-tocotrienol-induced EGR-1 by small interfering RNA attenuated δ-tocotrienol-induced Bax expression and reduced δ-tocotrienol-induced apoptosis. Further analyses showed that de novo protein synthesis was not required for δ-tocotrienol-induced EGR-1 expression, suggesting a direct effect of δ-tocotrienol on EGR-1 expression. Furthermore, a ChIP assay demonstrated that EGR-1 binds to the Bax gene promoter. Finally, δ-tocotrienol treatment induced Bax expression and activated EGR-1 in the pancreatic neoplastic cells of the PDX-Cre Kras genetically engineered model of pancreatic cancer. Our study provides the first evidence for EGR-1 as a direct target of vitamin E δ-tocotrienol, suggesting that EGR-1 may act as a pro-apoptotic factor in pancreatic cancer cells via induction of Bax.